A novel formation channel for supermassive black hole binaries in the early universe via primordial black holes - Zhang, Saiyang; Liu, Boyuan; Bromm, Volker (The astrophysical journal, 2025)
We present a novel formation channel for supermassive black hole (SMBH) binaries in the early Universe, driven by primordial black holes (PBHs). Using high-resolution hydrodynamical simulations, we explore the role of massive PBHs (mBH ∼ 106 M⊙) in catalyzing the formation of direct-collapse black holes (DCBHs), providing a natural in situ pathway for binary SMBH formation. PBHs enhance local overdensities, accelerate structure formation, and exert thermal feedback on the surrounding medium via accretion. Lyman-Werner radiation from accreting PBHs suppresses H2 cooling, shifting the dominant gas coolant to atomic hydrogen. When combined with significant baryon-dark matter streaming velocities (vbχ ≳ 0.8σbχ, where σbχ is the rms streaming velocity), these effects facilitate the formation of dense, gravitationally unstable atomically cooling gas clouds in the PBH’s wake. These clouds exhibit sustained high inflow rates ( yr−1), providing ideal conditions for DCBH formation from rapidly growing supermassive stars of ∼105 M⊙ at redshift z ∼ 20-10. The resulting systems form SMBH binaries with initial mass ratios and separations of ∼10 pc. Such PBH-DCBH binaries provide testable predictions for JWST and Atacama Large Millimeter/submillimeter Array, potentially explaining select high-z sources like little red dots, and represent gravitational-wave sources for future missions like LISA and TianQin—bridging early-Universe black hole physics, multimessenger astronomy, and dark matter theory.
Gesehen am 28.01.2026